Innovation Based Community Empowerment Program In Rural Area - Perdi Setiawan; Rohayati Suci Indrianingsih (Research Collaboration Community (RCC), 2020)
Efforts to encourage rural communities to have the ability and meet their own needs independently and have competitiveness can be done by empowering innovation-based communities in rural areas. With the village innovation program, it can support village development to be more effective and efficient through various innovation-based community empowerment programs to be more innovative and responsive to the needs of rural communities. The purpose of this study is to determine the implementation of innovation-based community empowerment programs in rural areas and the obstacles faced. The method used is Systematic Literature Review (SLR). The data used is sourced from journals searched through Google Scholar. The results of the review show that there are several innovation-based community empowerment programs in rural areas. Innovation-based empowerment programs have an important role for the welfare of rural communities. Recommendations that can be given are to give full attention to innovation-based empowerment programs for rural communities.